Reactivity of Peracetic Acid with Organic Compounds: A Critical Review - Kim, Juhee; Huang, Ching-Hua (ACS ES&T water, 2021)
As an emerging oxidant and disinfectant, peracetic acid (PAA) has increasingly been used in wastewater treatment and the food and medical industries and has attracted greater research interest. To better understand reactions initiated by PAA, this paper is among the first to comprehensively review the reactivity of PAA with respect to organic compounds of various structures. The reactivities of PAA with respect to 123 organic compounds are compiled from the literature and new experiments, and possible reaction pathways and products are discussed. Overall, PAA is an electrophile with high selectivity in reaction. The second-order rate constants of PAA oxidation of organic compounds vary by nearly 10 orders of magnitude, from 3.2 × 10–6 to >1.0 × 105 M–1 s–1, which are much larger than those of H2O2 coexisting in PAA solutions. Electron-donating groups of compounds increase the reactivity with respect to PAA, evidenced by the strong negative correlations between rate constants and substituent constants [Hammett (σ) or Taft (σ*)] of compounds. Sulfur moieties show exceptionally high reactivity with respect to PAA. Limited studies have shown that generally oxygen-added reaction products are formed from PAA oxidation. This critical review provides a useful foundation for advancing our understanding of the fate of organic compounds in wastewater treatment including PAA and identifies further research needs to evaluate a broader range of compounds and their oxidation products and toxicity.